Fifteen Years of the National Policy on Education: How far has language fared? - Bamgbose, Ayo (Centre for Language in Education and Development., 2014)
The role of language in education is usually taken for granted by linguists. Since acquisition of knowledge is most effectively carried out through the mediation of language, it comes naturally to linguists to assume that any educational policy must devote a substantial part to language.